Support to Rural Sanitation Scale Up Under the Philippine National Sustainable Sanitation Plan - World Bank (World Bank, Washington, DC, 2016)
This report summarizes the results and lessons learned from the Technical Assistance (TA) Support to Rural Sanitation Scale Up under the Philippine National Sustainable Sanitation Plan. The TA was carried out by the World Bank’s Water and Sanitation Program from July 2012 to March 2016, and is part of a larger programmatic assistance by the Bank to the Government of the Philippines in framing relevant institutional and financial reforms by key sector agencies and in strengthening the government’s capacity to accelerate delivery of basic water and sanitation services particularly to the poor. This synthesis report provides recommendations to consolidate and accelerate the scaling up rural sanitation initiative focusing on priorities for World Bank engagement and alignment with the incoming government’s overall strategic direction.